Future Translational Applications From the Contemporary Genomics Era. Issue 19 (12th May 2015) - Fox, Caroline S.; Hall, Jennifer L.; Arnett, Donna K.; Ashley, Euan A.; Delles, Christian; Engler, Mary B.; Freeman, Mason W.; Johnson, Julie A.; Lanfear, David E.; Liggett, Stephen B.; Lusis, Aldons J.; Loscalzo, Joseph; et al.
<x xml:space="preserve">Abstract</x> The field of genetics and genomics has advanced considerably with the achievement of recent milestones encompassing the identification of many loci for cardiovascular disease and variable drug responses. Despite this achievement, a gap exists in the understanding and advancement to meaningful translation that directly affects disease prevention and clinical care. The purpose of this scientific statement is to address the gap between genetic discoveries and their practical application to cardiovascular clinical care. In brief, this scientific statement assesses the current timeline for effective translation of basic discoveries to clinical advances, highlighting past successes. Current discoveries in the area of genetics and genomics are covered next, followed by future expectations, tools, and competencies for achieving the goal of improving clinical care.